Σύσταση καὶ ὀργάνωση ἑλληνικῶν κοινοτήτων στὴ Ρουμανία. Ἡ περίπτωση τοῦ Τζιούρτζιου καὶ τῆς Τουλτσέας (β΄ μισὸ 19ου αἰ.) - ΚΟΝΤΟΓΕΩΡΓΗΣ ΔΗΜΗΤΡΙΟΣ Μ. (Μνήμων, 2011)
The aim of this paper is to present comparatively the establishment in thesecond half of the 19th century of the Greek communities in the cities of Giurgiuand Tulcea as well as their statutes. One significant characteristic thatdifferentiates these two small and not that well-known communities from themajority of the Greek communities abroad was that from their very establishmentthey aimed to associate closely and ‘officially’ to the Greek state sincethe stipulations in both statutes allowed the Greek government, the Greekvice-consuls in particular, to intervene in the community’s function and internaladministration. After a thorough and in depth analysis of the historical circumstancesof the period and the place, the study attempts to track down thefactors which determined this interesting singularity.